Impact of breastfeeding on the intelligence quotient of the children of Rawalpindi, Pakistan - Khan, Shahrukh; Fatima, Syeda Nayab; Munir, Muhammad Arslan; Yousaf, Fizza; Kaynat, Wajeeha; Ishfaq, Maha; Khadim, Maida; Khan, Tayyab Mumtaz; Abid, Junaid; Akram, Jehanzeb (International Journal Of Community Medicine And Public Health, 2023)
Background: Breastfeeding impacts the children physical and mental growth and development. The impact of breastfeeding on intelligence quotient (IQ) of children is under-researched in Pakistan. This study aimed to determine the impact of breastfeeding on the intelligence quotient among children of Rawalpindi, Pakistan. Methods: This comparative cross-sectional was performed among 88 children of the Rawalpindi. Patients’ enrolment in the study was done via non-probability convenient sampling and developed inclusion and exclusion criteria. Ethical approval and informed consent were taken. Intelligence quotient was calculated through Wechsler intelligence scale for children (WISC). Data analysis was done via descriptive and inferential statistics by statistical package for the social sciences (SPSS) version 25. Chi square test was used to assess the variables association. P value less than 0.05 was set as statistically significant. Results: The overall mean score on WISC of intelligence quotient was 106 with SD of ±39, whereas, mean score of intelligence quotient for breastfed children was 112 with SD of ±32 and mean score of intelligence for children who were on formula milk was 100 with SD of ±36. The association between the type of milk and intelligence quotient (p=0.003) and association between duration of breastfeeding and intelligence quotient (p=0.04) was statistically significant. Conclusions: Children who had been on breastfeeding had better IQ. Furthermore, children who were breastfed for longer duration had even better IQ than children who were on breastfeeding for shorter duration.